PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN PEMBELAJARAN MIND MAPPING TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA SMP NEGERI 16 KUPANG - Korlina Muda Bota; St. Muthmainnah Yusuf; Nia Kurniaty Rukman (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2022)
The aim of this study was to develop valid mathematics learning media, practical, and effective categories with mind mapping learning method. This learning media was developed to improve students understanding concept in mathematics at SMP N 16 Kupang City. This study was Reaserch and Development (R&D). Products here were lesson plan (LP) and students’ worksheet (SW). The design of this study was ADDIE (Analyze, Design, Development, Implement,andEvaluate). The instrument here was validation sheet, students’ responsive questionary, and concept understanding test sheet. The result in term of valid category, this learning media was valid and the validation score for the first learning media was 3.42 and the second learning media 3,58. In term of practical category, this learning media was practical, so it can be used, and the average score of students’ responsive questionary was 84. In term of effectiveness, this learning media was very effective with score of 80%. Therefore, the development of learning media with mind mapping method to improve students concept understanding in mathematics for students at SMPN 16 Kupang city in this study was valid, practical, and effective, so it can be implemented in the learning process.